أحكام الشُّفعة بین الفقھ الإسلامي والقانون المدني الجزائري - قمولة, آسیة; ضو, مریم; قریرة, ھناء (University of Eloued-جامعة الوادي, 2014)
لقد عرفنا أنّ حق الشفعة هو حق ضعیف شرعا، ولا یثبت شرعا ولا قانونا إلاّ بتوافر أركانه وشروطه الشرعیة وإج ا رءاته القانونیة من وقت العلم بالبیع الحاصل بین البائع والمشتري وإلاّ سقط الحق في الشفعة، كما أنّ حق الشفعة هو حق لا یقبل التجزئة مطلقا فلا یجوز للشفیع الذي ثبتت له الشفعة أنیأخذ جزءا من العقار المشفوع، ویترك جزء منه ولو على جب ا ر المشتري ( لأن ذلك فیه ضر ا ر فاحشا بالمشتري) فإن الشفعة وحدة لا تتج أ ز إلا إذا تعدد الشفعاء واتحد العقار المشفوع فیه كان لكل واحد منهم أن یأخذ بنصیبه ویترك للآخرین نصیبا. summary We had known that the right of pre-emption is a weak right, and does not prove religiously neither legally. However, the availability of his ordinances, his terms of legitimacy, and his legal actions from the time that the seller and the buyer knows about the sale, otherwise, the right in taking the pre-emption is fall. Also the right of pre-emption accept never retail, and may not be the patron saint who prove his pre-emption to take a part of the property as supplemented and leaves a part of it. Even if against the buyer, because that has obscene damage for the buyer. The pre-emption indivisible unit but if multiplicity of the mediators and the unity of supplemented property. In this case, each one can take his share and leave a share for others
شريعة وقانون